Al pie de la letra: una aproximación al lenguaje verbal como parte constitutiva de la dimensión sonora de la música - Pablo Rojas Sahurie (Resonancias, 2021)
This article problematizes the status that verbal language has had in music, particularly in its sonorous dimension. For that purpose, it poses the relevance of rethinking the issue and reviews the musicological studies that address the relationship between music and verbal language. This paper thus reaches those positions which find a consistent link between the two. Nonetheless, these positions result in considering verbal language as an element that is associated, outside, next to or in front of the music, but not in it. Faced with the question of whether verbal language is outside of what we consider music, this paper argues that it is a constituent part of music at its sonorous level. To this end, it reviews the ontological reflections of Rajeev Patke, takes up the elements of musical semiotics supporting this theoretical approach, and reviews some approaches of the aural turn and the analogical hermeneutics of Mauricio Beuchot, which allow us to understand the problem proportionally. Consequently, the possibility of understanding verbal language as part of music arises insofar as verbal language sounds in an organized way through listening.